When Growth Is Not Enough : Explaining the Rigidity of Poverty in the Dominican Republic - Carneiro, Francisco Galrao; Sirtaine, Sophie (Washington, D.C.: World Bank, 2017)
The Dominican Republic stands out as a fast growing economy that has not been able to generate a commensurate reduction in poverty. Three reasons have been raised before to explain this conundrum: (i) a labor market that does not translate productivity gains into salary increases; (ii) a domestic economy with weak inter-sectoral linkages; (iii) and a public sector that does not spend enough nor particularly well to reduce poverty. In addition, the country remains largely exposed to natural disasters and exogenous shocks that, if not mitigated properly, may affect the sustainability of growth in the medium and longer terms. This book assembles a collection of empirical analyses that explore three complementary hypotheses that could help understand why the Dominican Republic continues, to this date, experiencing high economic growth rates with limited poverty reduction.